Protocol of secure key distribution using hash functions and quantum authenticated channels key distribution process six-state quantum protocol - Majeed, Mohammed Munther A.; Al-Khateeb, Khalid A. Saeed; Wahiddin, Mohamed Ridza; Saeb, Magdy M. (Science Publications, 2010)
Problem statement: In previous researches, we investigated the security of communication channels, which utilizes authentication, key distribution between two parties, error corrections and cost establishment. In the present work, we studied new concepts of Quantum Authentication (QA) and sharing key according to previous points. Approach: This study presented a new protocol concept that allows the session and key generation on-site by independently applying a cascade of two hash functions on a random string of bits at the sender and receiver sides. This protocol however, required a reliable method of authentication. It employed an out-of-band authentication methodology based on quantum theory, which uses entangled pairs of photons. Results: The proposed quantum authenticated channel is secure in the presence of eavesdropper who has access to both the classical and the quantum channels. Conclusion/Recommendations: The key distribution process using cascaded hash functions provides better security. The concepts presented by this protocol represent a valid approach to the communication security problem.